2007
DOI: 10.1002/elan.200704008
|View full text |Cite
|
Sign up to set email alerts
|

A Cobalt Film Electrode for Nitrite Determination in Natural Water

Abstract: In this study a cobalt film electrodeposited on a copper disk (˘¼ 3.1 mm) was tested as electrode to measure nitrite ions in raw water. This electrode was able to determine the nitrite ions concentration in nondeaerated synthetic media and in natural water. The electrode reached a detection limit of 0. , HCO 3 À and NH 4 þ was also tested. The electrode was used to determine the concentration of nitrite ions in a real sample.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…It is the inspiration as a driving force that had started the new activities in seeking analogues or alternatives to both BiFEs and BiEs. The result of such endeavors is a new family of metallic film electrodes and related configurations, namely: antimony film-and antimony powder-modified electrodes [201 -212], lead film- [213 -218], tin film- [219], gallium film- [220], cobalt film- [221], or even selenium film- [222] plated electrodes. Although almost all these electrodes mean a step back with respect to the "green-chemistry" concept, they may offer particular advantages in some specific applications.…”
Section: Conclusion: Bismuth Electrodes As Attractive and Inspiring Ementioning
confidence: 99%
“…It is the inspiration as a driving force that had started the new activities in seeking analogues or alternatives to both BiFEs and BiEs. The result of such endeavors is a new family of metallic film electrodes and related configurations, namely: antimony film-and antimony powder-modified electrodes [201 -212], lead film- [213 -218], tin film- [219], gallium film- [220], cobalt film- [221], or even selenium film- [222] plated electrodes. Although almost all these electrodes mean a step back with respect to the "green-chemistry" concept, they may offer particular advantages in some specific applications.…”
Section: Conclusion: Bismuth Electrodes As Attractive and Inspiring Ementioning
confidence: 99%
“…Among many electrode materials, copper is expected to be the most effective material in terms of electroreduction of nitrate and nitrite ions. [15][16][17][18][19][20][21] Indeed, many studies have shown that pretreated and/or modified copper electrodes are effective for the determination of nitrate and nitrite ions. 13,14,[22][23][24][25][26] However, the pretreatments and/or modifications of copper electrodes in the studies seem to be complicated, time consuming and insufficiently sensitive for the determination of nitrate and nitrite ions in natural water samples.…”
Section: Introductionmentioning
confidence: 99%
“…Nitrite can be found in water as a product of organic decomposition of wastes containing organic nitrogen into ammonium, which is then oxidized to nitrite and nitrate [1][2][3]. These processes may occur in treatment plants of water, the water distribution system and in natural waters.…”
Section: Introductionmentioning
confidence: 99%
“…This anion is an important precursor of nitrosamines, which are potential carcinogens responsible for potentially fatal blood disorder in infants under six months of age [4][5][6]. For this reason, the World Health Organization (WHO) recommends that drinking water does not contain nitrite in concentrations above 1 mg L À1 (NO 2 À ÀN) [1]. It is therefore an important challenge for environmental applications the development of simple, rapid and inexpensive analytical methods for the determination of nitrite at low concentrations.…”
Section: Introductionmentioning
confidence: 99%